Research on the Innovation of Procurement Mode of Nanomaterials Based on E-Commerce. (28th August 2022) - Song, Baorui; Wang, Xiaozhi
Abstract : With the rapid development of science and technology, the proportion of nanomaterials is increasing. With the advantages of height, strength, high density, and lightweight, nanomaterials have become the preferred manufacturing materials in many industries. In the procurement business of e-commerce, the utilization rate of nanomaterials is getting higher and higher. However, due to the long manufacturing cycle, high consumption loss, and high transportation damage rate of nanomaterials, there are often many problems in the procurement process. In this paper, we use the methods of case investigation and experimental research to study the innovation of procurement mode of nanomaterials in e-commerce. The data show that the use of nanomaterials has become the first choice of many manufacturers and suppliers and has a more and more frequent trend in the use process. Nanomaterials are suitable for industrial application due to their low transportation and storage costs and high procurement efficiency. However, at present, nanomaterials need further innovation to achieve more applications. In this paper, the procurement model and marketing model are innovated to make the e-commerce procurement business of nanomaterials more convenient. From these studies, this paper concludes that the most important thing for the procurement of nanomaterials is to find out the customers' needs, and then according to the user specifications of nanomaterials, achieve the best logistics and distribution methods in the transportation process. The innovation of the e-commerce procurement mode of nanomaterials can greatly facilitate the development of business. Under the innovative mode, the transportation cost and procurement efficiency have been greatly improved, about 2 points higher than before, and the procurement value has also increased by 3 points to more than 6 points. At the same time, the innovation of e-commerce procurement mode of nanomaterials can make the related upstream and downstream industrial chain reach a very saturated state and make the scientific and technological innovation and procurement salesman in the industry more smooth and reliable.